Literatur review: Analisis Customer Relationship Marketing Dan Strategi Pendukung Dalam Meningkatkan Loyalitas Pasien RS Serta Kaitannya Dengan Pandemi Covid-19 - Athiya Adibatul Wasi; Diansanto Prayoga (Dian Nuswantoro Semarang, 2022)
The COVID-19 pandemic has changed people's behavior to be reluctant to visit health facilities, especially hospitals. This has an impact on cash flow and makes hospital business competition more stringent, so it's necessary to determine a strategy to maintain patient loyalty. The purpose of this study to analyze the effect of customer relationship marketing on patient loyalty in hospital and identify supporting strategies that the hospital use as competitiveness with other hospitals. This research method is a literature study with inclusion criteria are journal discussing the topic of customer relationship marketing to patient loyalty in hospitals, and published between 2014-2020. The independent variable in this study is customer relationship marketing, and the dependent variable is patient loyalty. The database used are Google Scholar, Science Direct, and El Sevier. From database, 5 journals were obtained that were per the research objectives. Besides that, searching for news articles as supporting information. The results show a positive effect of customer relationship marketing on patient loyalty. Conclusion application of CRM still needs to be balanced with several indicators in developing a strategy, including infrastructure, management of product quality, service innovation, service quality, human resource management, ability to handle patient conflicts, and customer relationship management. Keywords : Customer Relationship Marketing, Patient loyalty, Pandemic Covid-19, Hospital, Strategies.